Diverse Roles of Ethylene in Regulating Agronomic Traits in Rice - Yin, Cui-Cui; Zhao, He; Ma, Biao; Chen, Shou-Yi; Zhang, Jin-Song (Frontiers in Plant Science, 2017)
Gaseous hormone ethylene has diverse effects in various plant processes. These processes include seed germination, plant growth, senescence, fruit ripening, biotic and abiotic stresses responses, and many other aspects. The biosynthesis and signaling of ethylene have been extensively studied in model Arabidopsis in the past two decades. However, knowledge about the ethylene signaling mechanism in crops and roles of ethylene in regulation of crop agronomic traits is still limited. Our recent findings demonstrate that rice possesses both conserved and diverged mechanism for ethylene signaling compared with Arabidopsis. Here, this review mainly focuses on the recent advances in ethylene regulation of important agronomic traits. Of special emphasis is its impact on rice growth, flowering, grain filling and grain size control. Similarly, the impact of ethylene on other relevant crops will be mentioned. Additionally, interactions of ethylene with other hormones will also be discussed in terms of crop growth and development. Increased insight into the roles and mechanisms of ethylene influencing agronomic traits will contribute to improvement of crop production through precise manipulation of ethylene actions in crops.